A spatial perspective to introducing biofortified staple food crops in Colombia - Funes, José; González, Carolina; Perez, S.; Birol, Ekin; Moursi, Mourad; Zeller, Manfred (European Association of Agricultural Economists, 2015)
Micronutrient malnutrition affects 2 billion people worldwide and biofortification—the process of breeding and delivering staple food crops with higher micronutrient content— could prove to be a cost-effective strategy for its alleviation. There is, however, a dearth of information on where and in which crop-micronutrient combinations to invest for this strategy to be most effective and yield the highest impact. To fill in this gap, a global biofortification index (BPI) was developed (Asare-Marfo et al., 2013). It is based on three sub-indexes, namely production, consumption, and micronutrient deficiency, all developed with subnational-level representative data. The Global BPI, however, is not granular enough to suggest within country investment opportunities for biofortification. In this paper we develop a methodology for a subnational-level BPI, using Colombia as a case study. In order to guide strategies for geographic targeting and intervention within country, we set statistical conditions for each sub-index and classify geographic targeted areas as areas of: (1) impact and intervention, (2) impact, or (3) intervention. To further identify geographic areas for intervention, a spatial interaction index derived from an economic gravity model is used. This spatial interaction index helps to identify and link foodsurplus and food-deficit areas. Our empirical results show that crops biofortified with zinc, namely white maize and rice, should be introduced in the North Coast of Colombia; crops biofortified with vitamin A, namely yellow maize and cassava, should be introduced primarily in the Atlantic and Amazon regions of the country. Introduction of iron-biofortified beans in the Andean region, especially Tolima and Antioquia, could have the greatest impact. Finally, we also estimate area- or population-weighted subnational BPIs, which, depending on the objective, takes into account the intensity of crop production as well as the proportion of people at risk of micronutrient deficiency. Funes, J.; González, C.; Birol, E.; Moursi, M.; Zeller, M.